Harnessing immunity for therapy in human papillomavirus driven cancers - Stern, Peter L. (Tumour Virus Res, 2021)
In persistent high-risk HPV infection, viral gene expression can trigger some important early changes to immune capabilities which act to protect the lesion from immune attack and subsequently promote its growth and ability for sustained immune escape. This includes immune checkpoint-inhibitor ligand expression (e.g. PD-L1) by tumour or associated immune cells that can block any anti-tumour T-cell effectors. While there are encouraging signs of efficacy for cancer immunotherapies including with immune checkpoint inhibitors, therapeutic vaccines and adoptive cell therapies, overall response and survival rates remain relatively low. HPV oncogene vaccination has shown some useful efficacy in treatment of patients with high-grade lesions but was unable to control later stage cancers. To maximally exploit anti-tumour immune responses, the suppressive factors associated with HPV carcinogenesis must be countered. Importantly, a combination of chemotherapy, reducing immunosuppressive myeloid cells, with therapeutic HPV vaccination significantly improves impact on cancer treatment. Many clinical trials are investigating checkpoint inhibitor treatments in HPV associated cancers but response rates are limited; combination with vaccination is being tested. Further investigation of how chemo- and/or radio-therapy can influence the recovery of effective anti-tumour immunity is warranted. Understanding how to optimally deploy and sequence conventional and immunotherapies is the challenge.